Young people's sexual readiness: insights gained from comparing a researchers' and youth advisory group's interpretation. Issue 9 (1st September 2020) - Templeton, Michelle; Lohan, Maria; Lundy, Laura; Kelly, Carmel
Abstract: This study explored young people's understandings of sexual readiness and what influenced their decision to initiate first sex. Interviews conducted with 20 heterosexual young people aged 16–18 years, attending sexual health clinics in Northern Ireland, were analysed using a combined approach. This included comparing a researchers and youth advisory group's interpretations of the same data. Thematic analysis enabled comparison to draw out insights across both interpretations. Three themes emerged from each analysis that aligned closely with one another: Mental/Intimate Contact; People/Peer Influences; Self/Socio-Cultural Influences. One additional theme, Adult Control, emerged from the researchers' understanding alone. Results suggest that young people actively deliberate about sex as inevitable and find it difficult to resist the peer and social influences that regulate their lives, with many initiating sex 'to-get-it-over-with'. Gender ideologies and relationship status influenced expectations, motivations and the context surrounding first sex. Sexual readiness was informed by whether first sex was 'good', 'not so good' or 'bad', highlighting the gaps in young people's understanding. Health, law, and education sectors should co-produce interventions with young people to provide relevant and realistic information that explores the effects of gender equality in everyday life on related concepts such as respect, rights, responsibility and resilience.